2015
DOI: 10.15537/smj.2015.6.10888
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries in primary and permanent teeth and its relation with tooth brushing habits among schoolchildren in Eastern Saudi Arabia

Abstract: Objectives:To determine the prevalence of dental caries in the primary and permanent teeth, and evaluate the brushing habits of school children in Dammam, Kingdom of Saudi Arabia (KSA).Methods:This study was conducted at Dammam, KSA. Oral examination of the participants was conducted from February to May 2014. The total sample size for this cross-sectional study was 711. There were 397 children between the age of 6-9 years, who were examined for primary teeth caries, and 314 between the age 10-12 years were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
79
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 14 publications
16
79
3
3
Order By: Relevance
“…13 But this finding is in contrast to another study. 10 There was significant difference in the prevalence of dental caries in private school children and government school children which is similar to other studies. 7,14 Among the studied population, 5 to 10 years had maximum number of decayed teeth compared to 11 to 15 years' age groups with negligible filled component.…”
Section: Jcms Nepal 2017;13(2):275-8 Prevalence Of Dental Caries Amonsupporting
confidence: 88%
“…13 But this finding is in contrast to another study. 10 There was significant difference in the prevalence of dental caries in private school children and government school children which is similar to other studies. 7,14 Among the studied population, 5 to 10 years had maximum number of decayed teeth compared to 11 to 15 years' age groups with negligible filled component.…”
Section: Jcms Nepal 2017;13(2):275-8 Prevalence Of Dental Caries Amonsupporting
confidence: 88%
“…In the current study, the mean dmft index in caries-affected children was nearly consistent with Farooqi et al, (2015) [45] who reported 3.66±3.13 mean dmft value among Saudi children. While the mean DMFT index in caries-affected children was 1.69 ± 1.14, which confirms the data of a previous study on the caries prevalence in 7-11-years-old Saudi primary school children in Riyadh where the DMFT index was 1.6 ± 1.5 [47] .…”
Section: Discussionsupporting
confidence: 88%
“…This observation is consistent with a study carried out on 6-15-years-old school children in Jazan, Saudi Arabia, where caries prevalence was 91.3% [44] . Whereas, in Dammam, caries prevalence was 73% among school children aged 6-12 years [45] .…”
Section: Discussionmentioning
confidence: 85%
“…Special considerations are needed for children in general, but in particular for countries with a high caries prevalence accompanied by a minimum prevention protocol. As mentioned by Farooqi et al [2015], the caries level in Saudi Arabia is still high compared with the WHO oral health goals, and special preventive measures and instructions should be given to schools, parents, and children when it comes to appropriate oral hygiene and dietary habits.…”
mentioning
confidence: 99%